2013
DOI: 10.1159/000362621
|View full text |Cite
|
Sign up to set email alerts
|

Exophytic Glioma of the Medulla: Presentation, Management and Outcome

Abstract: Objective: Exophytic gliomas of the medulla are rare childhood tumors that mostly are pilocytic astrocytomas. Here we report our experience in 11 ‑children with this rare tumor. Methods: A retrospective study was performed using the records of children with exophytic gliomas of the medulla at Children's Hospital Medical Center in Tehran, Iran, from 2002 through 2013. The general, clinical, and radiological data and follow-up of all patients were reviewed. Results: The patients mostly were male aged from 11 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Similar to our results, most authors concluded that, in cases of exophytic brain stem gliomas, a gross total or subtotal removal with a favorable prognosis is possible in most patients [18].…”
Section: Surgical Strategysupporting
confidence: 91%
“…Similar to our results, most authors concluded that, in cases of exophytic brain stem gliomas, a gross total or subtotal removal with a favorable prognosis is possible in most patients [18].…”
Section: Surgical Strategysupporting
confidence: 91%
“…Two articles were written in Persian [8, 12], whereas the remaining 33 were written in English. Most studies (n = 27) took place in Tehran province [4–5, 8, 1113, 15–23, 25–29, 3137] in hospitals and centers affiliated with the three main medical universities in Tehran: Tehran University of Medical Sciences (n = 16) [4–5, 11, 13, 1617, 1922, 26, 2829, 3132, 37], Shahid Beheshti University of Medical Sciences (n = 6) [12, 15, 18, 25, 27, 34,], Iran University of Medical Sciences (n = 4) [8, 23, 35, 36], and Army University of Medical Science (n = 1) [33]. Only four articles [18, 23, 26, 34] stated that approval by an ethics committee had been obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The study objectives were categorized as clinical (n = 18 articles, 173 patients), epidemiologic (n = 9 articles [5, 8, 12–13, 16, 26, 28, 33–34], 1,881 patients), pathologic (n = 4 articles [11, 14, 15, 18], 1,160 patients), genetic (n = 2 articles [7, 30], 75 patients), surgical (n = 1 article [21], 172 patients), or radiologic (n = 1 article [29], 23 patients). Study designs were primarily single case reports (n = 16 articles [2–4, 9, 1617, 1922, 24, 29, 3132, 3637], 19 patients) and cross-sectional studies (n = 15 articles [7–8, 10–14, 15, 18, 25–26, 28, 30, 33–34], 3,271 patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations